2020
DOI: 10.15517/lank.v20i2.41823
|View full text |Cite
|
Sign up to set email alerts
|

Dracula irmelinae, a new species in the subtribe Pleurothallidinae (Orchidaceae) from the Western Andes of Colombia

Abstract: A new species of Dracula (Pleurothallidinae: Orchidaceae) from Colombia is described, honoring Irmelin Indenbirken, mother of the actor and philanthropist Leonardo DiCaprio. D. irmelinae is phenotypically most similar to Dracula verticulosa, but differs in having larger and wider sepals that form a smoothly curved semicircular mentum behind the lip, an indumentum with dark red internal and external maculae and dense long pubescence on the internal sepal surfaces and bases of the tails. The geographic distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Morphological variation has been documented in other Dracula species. For instance, Peláez et al (2020) found that Dracula irmelinae presents natural variation of flower morphology, indumentum pigmentation, sepal width, and lip aspect ratios and symmetry. Nonetheless, there is a big challenge ahead to clearly identify the origin of this intraspecific morphological plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological variation has been documented in other Dracula species. For instance, Peláez et al (2020) found that Dracula irmelinae presents natural variation of flower morphology, indumentum pigmentation, sepal width, and lip aspect ratios and symmetry. Nonetheless, there is a big challenge ahead to clearly identify the origin of this intraspecific morphological plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Dracula Luer is a genus in the Orchidaceae family (subtribe 5 Pleurothallidinae; Luer 1993), which includes 134 accepted species, with species discovered frequently, even in extensively surveyed sites (Pel aez et al 2009;Baquero and Meyer 2014). Dracula is distributed across Neotropical cloud forests, from southern Mexico to Peru, but it is most diverse in the Colombian Andes with 75 species (Calderon-Saenz 2007;Pel aez et al 2020). However, there is uncertainty about the identity of several Dracula species due to a lack of information from naturally occurring populations.…”
mentioning
confidence: 99%